Association between body shape index and body mass index with knee osteoarthritis: a case control study - Anik Nurmalikah; Ulfa Elfiah; Nindya Shinta Rumastika; Yuli Hermansyah; Dwita Aryadina Rachmawati (Universitas Udayana, 2025)
Background and purpose: Being overweight or obese, which can be determined using the body mass index (BMI), is one of the risk factors for knee osteoarthritis (KOA). Whilst, body shape index (BSI) is considered as more accurate indicator, hence, this study aims to assess correlation of BSI and BMI with KOA. Methods: This study employed a case control design conducted in Jenggawah Village, East Java. Samples were randomly taken from the social service program of the Faculty of Medicine, University of Jember which conducted on June 18, 2023, included 30 KOA patients and 30 non-KOA patients who met the inclusion and exclusion criteria. The instruments used were Omni Calculator and KOA clinical criteria sheet. The statistical analysis used the Spearman Rank correlation test with a significance level of p<0.05. Results: The statistical analysis revealed a significant, moderate, and direct correlation between BSI and KOA (p=0.002; r=0.391). On the other hand, BMI showed an insignificant, very weak, and inverse correlation with KOA (p=0.432; r=-0.103). BSI values indicate low amount of skeletal muscle mass with increased visceral or abdominal adiposity. BMI only assesses overweight, while BSI can represent central adiposity, which also affects KOA. Conclusion: The study concludes that BSI is related to the incidence of KOA, while BMI is not related to the incidence of KOA in Jenggawah Village, Jember Regency. Future research could use a cohort plan to validate whether BMI and BSI can predict the incidence of KOA.